Phylogenetic relationships between Asplenium bourgaei (Boiss.) Milde and A. jahandiezii (Litard.) rouy inferred from morphological characters and rbcL sequences - Schulze, Gerhard; Treutlein, Jens; Wink, Michael (Plant biology, 2001)
Abstract: Micromorphological analysis reveals that A. jahandiezii, which occurs as a local endemic taxon in the Grand Canyon du Verdon in southern France, shows substantial differences to A. bourgaei, from the eastern Mediterranean region, in the surface structure of perispores, sporangial indehiscence and the size of stomatal subsidiary cells. Nucleotide sequences and genetic distances (0.9 % nucleotide substitutions) of the rbcL gene support the view that both taxa are related but distinct sibling species. Both species form a monophyletic group together with Asplenium fontanum and A. majoricum.